Educational attainment inequalities in depressive symptoms in more than 100,000 individuals in Europe - Chlapecka, Adam; Kagstrom, Anna; Cermakova, Pavla (European psychiatry, 2020)
BACKGROUND: Increasing educational attainment (EA) could decrease the occurrence of depression. We investigated the relationship between EA and depressive symptoms in older individuals across four European regions. METHODS: We studied 108,315 Europeans (54% women, median age 63 years old) from the Survey on Health, Ageing and Retirement in Europe assessing EA (seven educational levels based on International Standard Classification of Education [ISCED] classification) and depressive symptoms (≥4 points on EURO-D scale). Logistic regression estimated the association between EA and depressive symptoms, adjusting for sociodemographic and health-related factors, testing for sex/age/region and education interactions. RESULTS: Higher EA was associated with lower odds of depressive symptoms, independent of sociodemographic and health-related factors. A threshold of the lowest odds of depressive symptoms was detected at the first stage of tertiary education (OR 0.60; 95% confidence interval [CI] 0.55-0.65; p < 0.001; relative to no education). Central and Eastern Europe showed the strongest association (OR for high vs. low education 0.37; 95% CI 0.33-0.40; p < 0.001) and Scandinavia the weakest (OR for high vs. low education 0.69; 95% CI 0.60-0.80; p < 0.001). The association was strongest among younger individuals. There was a sex and education interaction only within Central and Eastern Europe. CONCLUSIONS: Level of EA is reflected in later-life depressive symptoms, suggesting that supporting individuals in achieving EA, and considering those with lower EA at increased risk for depression, could lead to decreased burden of depression across the life course. Further educational support in Central and Eastern Europe may decrease the higher burden of depressive symptoms in women.
Keywords: Logistic Models; Europe, Eastern; Male; Aging; epidemiology; důchod; education; Europe; Aged; mužské pohlaví; senioři; deprese; sociální determinanty zdraví; stupeň vzdělání; logistické modely; Evropa; lidé; ženské pohlaví; Educational Status; Humans; Retirement; stárnutí; Social Determinants of Health; východní Evropa; Female; Depression; lidé středního věku; Middle Aged